A Comprehensive Review of In-Situ Monitoring and Post-Process Defect Detection in Additive Manufacturing - Tunji J. ERINLE; Daniel C. UGURU-OKORIE; Abiodun M. ADEBIMPE; Adeolu A. ADEDIRAN; Hilary U. EZEA (FUDMA Journal of Engineering and Technology, 2026)
Additive manufacturing (AM) technology has revolutionised the creation of metal and polymer parts within aerospace, biomedical, automotive, and energy industries; however, susceptibility to defects has hindered certification and implementation within industry. This study provides a critical review of in-situ monitoring and post-processing defect detection methods within AM. In contrast to the existing review literature which solely discusses techniques by domestic, this study aims to add value by providing a Technology Readiness Level (TRL) rating (1-9) of 12 techniques, a unique defect-technique mapping approach with detectability ratings (1-5), and an innovative decision framework with an ability to minimise the amount of post-processing inspections by up to 40-60%. The defects, including porosity, lack of fusion, cracking, delamination, and distortion, are classified according to powder bed fusion, directed energy deposition, and extrusion-based methods of additive manufacturing. Some of the main gaps revealed in this review include a lack of validated fusion models, certification pathways allowing for the use of in-situ data, and low industry TRL (3-4) for combined multisensor monitoring systems. Future research areas include benchmarking data sets, standards within ASTM F42/ISO/ASTM 52900, and closed-loop control systems.